THE EFFECT OF COPPER ELECTRIC AND ZINC VARIATIONS ON THE PRODUCTIVITY OF MICROBIAL FUEL CELL (MFC) ELECTRICAL WASTE SUBSTRATES IN LIQUID WATER WASTE INSTANT NOODLES - Muhammad Islam Ramadhani; Aqli Mursadin Mursadin (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2020)
MFC is a system of generating electricity by utilizing bacterial interactions found in nature. The bacteria found in organics convert organic matter into electrical energy. The nature of bacteria that can degrade organisms in MFC produces electron and proton ions. These ions produce differences in electrical potential so that energy can be produced. The purpose of this study was to determine the electrical potential of instant noodle stew wastewater and the effect of electrodes on the acquisition of electricity using copper and zinc electrodes and a combination of copper and zinc, and to know the effect of aerators on MFC. This research was conducted for 12 hours and data collection was done once every hour for 12 hours. The instant noodle boiled water with a combination of zinc and copper (Zn-Cu) electrodes produces more electricity than other electrode combinations. The combination of copper and zinc electrodes (Cu-Zn) produces the lowest electricity gain and cannot be used as a combination of electrodes. At Cu-Cu electrodes obtained were 313 mA and 498 mV, on Zn-Zn electrodes obtained were 106 mA and 100 mV, on Zn-Cu electrodes obtained were 1393 mA and 941 mV.